INFLUENCE OF COMMONLY USED HEAT TREATMENTS OF ROW MILK ON PRESENCE AND NUMBER OF COAGULASE-POSITIVE STAPHYLOCOCCI - Bešić, Adna; Karakaš, Sead; Čaklovica, Kenan; Mušović, Adisa; Sultanović, Mehmed; Smajović, Alisa; Katica, Muhamed (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background: positive staphylococci (CPS) are common contaminants of raw milk. Before it is used, various heat treatments are applied to destroy microorganisms, inactivate enzymes and improve technological properties and concentration of dry matter of milk. This work aimed to determine the influence of commonly used heat treatments in diary on presence and number CPS in raw milk from Bosnia and Herzegovina area and to affirm whether there is a difference in efficacy between different treatments. Method: Using the standard method, 40 samples of raw milk from farms were inoculated for counting the initial number of CPS in raw milk. Samples were then exposed to heat treatments in vapor sterilizer and CPS number was counted using the same standard method. Results: Applied treatments included heat treatments at: 68 °C/40 s, 70 °C/15 s, 72 °C/without holding, 63 °C/30 min and 72 °C/15 s. CPS presence was detected in all tested samples of raw milk in numbers ranging from 2,82 to 5,32, with an average of 4,30, calculated as log10 /ml. Conclusions: Raw milk samples collected in the field initially registered a high CPS number. The applied heat treatments were effective to a large extent. The initial CPS count of milk seems to be the most important factor determining the number of CPS after heat treatments as well as traits of the strains.